Proteins in food processing - Yada, R. Y. 1954- (CRC Press ; Woodhead Pub., 2004)
Proteins are essential dietary components and have a significant effect on food quality. Edited by a leading expert in the field and with a distinguished international team of contributors, Proteins in food processing reviews how proteins may be used to enhance the nutritional, textural and other qualities of food products. After two introductory chapters, the book first discusses sources of proteins, examining the caseins, whey, muscle and soy proteins and proteins from oil-producing plants, cereals and seaweed. Part 2 illustrates the analysis and modification of proteins, with chapters on testing protein functionality, modelling protein behaviour, extracting and purifying proteins and reducing their allergenicity. A final group of chapters are devoted to the functional value of proteins and how they are used as additives in foods.
Keywords: Proteins in human nutrition.; Food industry and trade.; Proteins.; elektronické knihy; electronic books